2011
DOI: 10.1177/1066896911429296
|View full text |Cite
|
Sign up to set email alerts
|

Depolarized MUC1 Expression Is Closely Associated With Hypoxic Markers and Poor Outcome in Resected Non–Small Cell Lung Cancer

Abstract: MUC1 is transmembrane mucin aberrantly overexpressed in various cancers. However, little is known about how MUC1 expression is associated with hypoxia, glucose metabolism, and epidermal growth factor receptor (EGFR) pathway, which are related to cancer progression. The aim of this study is to evaluate the relationship between MUC1 expression and these molecular markers in lung cancer. Of all 126 patients, high-grade polarized expression (HP), low-grade polarized expression (LP), and depolarized expression (DP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
100
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 27 publications
9
100
3
Order By: Relevance
“…9 MUC1 expression is seen in all subtypes of breast cancer, including luminal, HER2 + studies in metastatic breast, colorectal, gall bladder, non-small cell lung and gastric cancer, using KL-6, discovered that MUC1 expression at the circumference of the plasma membrane and/or in the cytoplasm frequently correlated with deep invasion, lymph node or liver metastasis and decreased five-year survival. [40][41][42][43] These studies demonstrate that MUC1 detection in patient circulation and localization of expression in the tumor are important prognostic factors for metastasis and disease progression.…”
Section: Muc1 Expression Correlates With Metastasismentioning
confidence: 80%
“…9 MUC1 expression is seen in all subtypes of breast cancer, including luminal, HER2 + studies in metastatic breast, colorectal, gall bladder, non-small cell lung and gastric cancer, using KL-6, discovered that MUC1 expression at the circumference of the plasma membrane and/or in the cytoplasm frequently correlated with deep invasion, lymph node or liver metastasis and decreased five-year survival. [40][41][42][43] These studies demonstrate that MUC1 detection in patient circulation and localization of expression in the tumor are important prognostic factors for metastasis and disease progression.…”
Section: Muc1 Expression Correlates With Metastasismentioning
confidence: 80%
“…The tumors in which the stained tumor cells were scored as 3, 4, or 5 were defined as positive; tumors scoring 4 or 5 were defined as having high expression. The immunohistochemical staining for CD34, Ki-67, and p53 was performed according to the procedures described in the previous reports [18][19][20]. The following antibodies were used: mouse monoclonal antibodies against CD34 (Nichirei, Tokyo, Japan; 1:800 dilution), Ki-67 (Dako, Glostrup, Denmark; 1:40 dilution), and p53 (D07; Dako; 1:50 dilution).…”
Section: Patientsmentioning
confidence: 99%
“…The anti-CD98 antibody used is an affinity-purified rabbit polyclonal antibody (Santa Cruz Biotechnology, Inc.; 1:100 dilution) raised against a peptide mapping to the carboxy terminus of human CD98. The detailed protocol for immunostaining has been published elsewhere [18][19][20]. The LAT1 and CD98 expression scores were defined by the extent of staining as follows: 1, ≤ 10 % of tumor area stained; 2, 11-25 % stained; 3, 26-50 % stained; 4, 51-75 % stained; and 5, ≥76 %.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we examined the relative expression levels of amino acid transporter genes L-type amino acid transporter 1 (LAT1), LAT2 and h4F2hc. LAT1, as a transporter gene, is reported to be highly expressed in various human cancers (26)(27)(28)(29)(30)(31)(32), and its expression is strongly correlated with that of another amino acid transporter gene, h4F2hc (26). We performed qRT-PCR to determine transporter gene expression after 48 h of low-glucose culture and found that the decrease in glucose concentration led to the significant upregulation of amino acid transporters (LAT1 and h4Fhc).…”
Section: Overexpression Of Amino Acid Transporter Genes Induced By Glmentioning
confidence: 99%